2012
DOI: 10.1007/s10278-012-9511-5
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Noise in Positron Emission Tomography Images Reconstructed with Filtered-Backprojection and Row-Action Maximum Likelihood Algorithm

Abstract: Noise levels observed in positron emission tomography (PET) images complicate their geometric interpretation. Post-processing techniques aimed at noise reduction may be employed to overcome this problem. The detailed characteristics of the noise affecting PET images are, however, often not well known. Typically, it is assumed that overall the noise may be characterized as Gaussian. Other PET-imaging-related studies have been specifically aimed at the reduction of noise represented by a Poisson or mixed Poisson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…3 A and B. In the present study, the FBP images show no skewness supporting the Gaussian distribution consistent with previous studies [22]. By contrast, the IR images show skewness particularly in the early time frames (Fig.…”
Section: A Physical Phantom Datasupporting
confidence: 79%
See 2 more Smart Citations
“…3 A and B. In the present study, the FBP images show no skewness supporting the Gaussian distribution consistent with previous studies [22]. By contrast, the IR images show skewness particularly in the early time frames (Fig.…”
Section: A Physical Phantom Datasupporting
confidence: 79%
“…Using quantile-quantile (Q-Q) plots and less formal statistical methods, Teymurazyan et al [22] showed that the noise in RAMLA-reconstructed PET images was well characterized by the Gamma distribution while FBP reconstructions produced comparable conformity with both normal and Gamma statistics. This study uses a more formal likelihood based approach to investigate evidence in support of the Gamma model in the EM and FBP reconstructed images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positron emission itself is characterized statistically by a Poisson distribution (7). Even if the same object is scanned, the same image cannot be obtained because of the statistical fluctuation (8).…”
mentioning
confidence: 99%
“…Similarly, the spatial resolution in PET is typically between 3 to 5 mm and, thus, PET data sets are relatively small as well. Noise in SPECT and PET systems are due to several factors including the Poisson distributed noise during emission, electronic noise in the scanner's detection system, and the noise alterations due to the post-processing corrections and the image reconstruction process [24].…”
Section: Nuclear Imagingmentioning
confidence: 99%